2011
DOI: 10.1111/j.1525-1470.2011.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol versus Prednisone in the Treatment of Infantile Hemangiomas: A Retrospective Comparative Study

Abstract: The goal of the current study was to compare the clinical effectiveness of oral propranolol with that of oral prednisone in the treatment of infantile hemangiomas (IH). Patients treated for IH with oral propranolol were retrospectively matched with patients treated with oral prednisone according to type, location, and size of the IH and age at start of treatment. Response to treatment was evaluated by rating serial medical photographs taken 1, 2, and 6 months after initiation of treatment. Degree of clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 17 publications
3
61
0
2
Order By: Relevance
“…Regarding distribution of Infantile hemangioma in different parts of the body 67.34% were in head-neck and face (face, orbital/periorbital, scalp, lip) region in our study which were cosmetically very much important site. In Anand Pandeyet al2009 study most of cases lesions were in head and face region (64.9%) 10 . According to Sans et al2009, Smithers and Fishman.2010 most of the lesion were in the same area 60% and 63% respectively 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding distribution of Infantile hemangioma in different parts of the body 67.34% were in head-neck and face (face, orbital/periorbital, scalp, lip) region in our study which were cosmetically very much important site. In Anand Pandeyet al2009 study most of cases lesions were in head and face region (64.9%) 10 . According to Sans et al2009, Smithers and Fishman.2010 most of the lesion were in the same area 60% and 63% respectively 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies used a visual analog scale. 22,24,28 Ten studies used a subjective rating of response (eg, good, fair, poor; complete, partial, no response), typically with a percentage improvement related 3 15,16,18,20,23,25,26,[29][30][31] Two studies rated improvement as greater or less than either 50% 32 or 75%. 21 The additional studies reported percent reduction, 27 change in total surface area, 19 or mean percentage decrease in size.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…18 Two RCTs and 2 cohort studies compared oral propranolol (2.0-2.7 mg/kg/day) and oral prednisolone or oral prednisone (2-4 mg/kg/day). [19][20][21][22] One cohort study compared oral propranolol (2 mg/kg/day) and intralesional bleomycin (0.5 mg/kg) 23 ; and 1 RCT and 1 cohort study evaluated oral propranolol (2-3 mg/kg/day) and other β-blockers (1-4 mg/kg/ day). 24,25 Three cohort studies and 2 RCTs assessed topical timolol (0.5%) compared with placebo or observation or another agent, [26][27][28][29][30] and 1 RCT and 1 cohort study evaluated different steroids, including oral prednisone and intralesional triamcinolone.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations